Can aura migraine be elicited by isolated pulmonary arteriovenous fistula?—A case report - Onorato, Eustaquio Maria; Salvia, Josephal; Becchina, Mariano; Cipolla, Tommaso; Anzola, Gian Paolo (Frontiers in Neurology, 2022)
A pulmonary arteriovenous fistula (PAVM) is an abnormal blood vessel that creates a direct connection between a pulmonary artery and its tributary vein bypassing capillary filter, establishing as a consequence of a low-resistance right-to-left shunting (RLS). The vast majority of PAVMs are congenital appearing more often in females than in males. A great number of patients with PAVMs is suffering concurrently from hereditary hemorrhagic telangiectasia (HHT) whose incidence is around 1 in 5,000. Very few cases of acquired PAVMs have been described in the literature. Paradoxical embolism through PAVMs can cause systemic desaturation, cyanosis, and serious cerebrovascular ischemic events (transient ischemic attacks, strokes, and intracranial abscess), even when the abnormal blood vessel is small (diameter <3 mm). Notably, it has been reported a high prevalence of aura migraine (MHA) symptoms in patients with PAVMs and concomitant HHT. We described in this study the case of a young aura migraineur female patient without HHT in whom isolated PAVM below the detection limit of pulmonary angiography and chest computed tomography angiography (CTA) has been documented by contrast Transthoracic and Transesophageal Echocardiography (cTTE/TEE) showing a delayed (>17 s) RLS coming from left pulmonary veins to left atrium while a patent foramen ovale (PFO), small atrial septal defects or septum primum fenestration could not be detected despite several attempts. Contrast Transcranial Doppler (cTCD) confirmed a delayed (>16 s) RLS with two short “shower” patterns corroborating the diagnosis of an extra-cardiac RLS. During the right heart catheterization and pulmonary angiography, it was impossible to cross the interatrial septum with a multipurpose catheter. The patient was finally discharged with off-label thienopyridine agents (clopidogrel 75 mg die) in terms of primary prophylaxis for paradoxical right-to-left embolization of thrombotic material ultimately. Aura migraine symptoms were nearly abolished by P2Y12 platelet inhibition, suggesting a platelet-based mechanism. During 2 years of clinical follow-up on thienopyridine therapy, the resolution of aura migraine episodes was definitively accomplished with significant improvement in her quality of life.